Credit Guarantee Schemes Supporting Small Enterprise Development: A Review - Samujh, Ruth-Helen; Twiname, Linda; Reutemann, Jody (Asian Journal of Business and Accounting, 2012)
Access to finance has become increasingly difficult, particularly for new and service-based industries without tangible assets to use as security. Globally, credit guarantee schemes (CGS) are seen as important instruments to facilitate achievement of national economic goals, as they enable entrepreneurs to gain access to finance for venture creation and development. We reviewed CGS literature between 1990 and early 2011. We discovered largely descriptive studies on the various conditions of the guarantees, and considerable research gaps. The desirability of CGS appears to be assumed whilst measurement of CGS performance provides ambiguous results. We recommend research in a variety of areas including: identification of factors that minimise risk, the impacts of varying risk sharing ratios, unintended CGS consequences, reporting the social dimensions, valuing intangibles, default rates in Asian countries, and collateral in a knowledge based economy. Keywords: Micro-finance, Loan Securitisation, Small Enterprise finance, Loan Guarantee, Credit Guarantee, Collateral, Micro-credit